2012
DOI: 10.1186/1471-2458-12-528
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer screening knowledge, attitudes and behavioural intention among Indigenous Western Australians

Abstract: Background Indigenous Australians are significantly less likely to participate in colorectal cancer (CRC) screening compared to non-Indigenous people. This study aimed to identify important factors influencing the decision to undertake screening using Faecal Occult Blood Testing (FOBT) among Indigenous Australians. Very little evidence exists to guide interventions and programmatic approaches for facilitating screening uptake in this population in order to reduce the disparity in colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
71
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 45 publications
15
71
3
2
Order By: Relevance
“…4 Previous studies assessing the awareness of CRC in several aspects, including epidemiology, symptoms/signs, and risk factors have revealed a poverty in the knowledge of the public, which is disconcerting given the fact that CRC still remains largely a topic of confusion in the general population.This has contributed significantly to the deleterious consequences on time of presentation and, therefore, on overall survival. [5][6][7][8][9][10][11] These findings were also consistent with the data of another study, which showed that the level of CRC knowledge among the Saudi general public was low, thus signifying the necessity of continuing public education and screening programs. 12 Furthermore, the lack of awareness was not only reported among the general public, but even more among patients following up in thegastroenterology clinics and the peripheral colorectal surgical unit.…”
Section: Issn: 2320-5407supporting
confidence: 81%
“…4 Previous studies assessing the awareness of CRC in several aspects, including epidemiology, symptoms/signs, and risk factors have revealed a poverty in the knowledge of the public, which is disconcerting given the fact that CRC still remains largely a topic of confusion in the general population.This has contributed significantly to the deleterious consequences on time of presentation and, therefore, on overall survival. [5][6][7][8][9][10][11] These findings were also consistent with the data of another study, which showed that the level of CRC knowledge among the Saudi general public was low, thus signifying the necessity of continuing public education and screening programs. 12 Furthermore, the lack of awareness was not only reported among the general public, but even more among patients following up in thegastroenterology clinics and the peripheral colorectal surgical unit.…”
Section: Issn: 2320-5407supporting
confidence: 81%
“…In comparison to other countries, similar low levels of knowledge about prevention of CRC have been reported [17,[20][21][22]. For example in Italy, a target population of adults identified colonoscopy and FOBT as main screening tests for prevention of CRC at 62% and 52% respectively [24].…”
Section: Discussionmentioning
confidence: 72%
“…CRC are easily prevented through CRC screening which can detect the disease during its early stages when the survival rates are high [17]. In order to create targeted messages and educational material aimed to booster participation in screening, it is required to understand the levels of knowledge, attitudes and beliefs of the target population [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 A woman's belief in the benefit of screening may be influenced by her social network, her health care providers, and the media. 12,13 Women who have a regular health care provider and who undergo routine checkups may discuss the benefit of early detection with their providers, who usually recommend screening. Media can have a positive influence by reporting women's success stories in which cancers are detected early and successfully treated or a negative influence by reporting conflicting recommendations regarding screening guidelines or by casting doubt about the value of screening.…”
Section: Introductionmentioning
confidence: 99%